PENGARUH LATAR BELAKANG PENDIDIKAN ORANG TUA TERHADAP HASIL BELAJAR SISWA KELAS III SD INPRES 44 KABUPATEN SORONG - Desy Puspa Ndari; Syams Kusumaningrum; Ahmad Yulianto (JIP: Jurnal Ilmu Pendidikan, 2025)
The purpose of this study is to ascertain how the educational backgrounds of the parents affect the learning results of the third-grade pupils at SD Inpres 44 Sorong Regency. The research methodology used in this study is quantitative. All third-grade students at SD Inpres 44 Sorong Regency made up the study's population. A questionnaire about the educational attainment of parents of third-graders at SD Inpres 44 Sorong Regency served as the data collection tool. The study's findings demonstrated that the only students with high category learning outcomes in the Indonesian Language subject are those whose parents have completed high school and S1. These students are enrolled in grade III SD Inpres 44 Sorong Regency. Learning outcomes in the Indonesian language subject fall into a sufficient category for students whose parents have completed junior high school, while learning outcomes in the same subject fall into a very low and concerning category for students whose parents have completed elementary school. The study's findings suggest that parents' educational backgrounds have a significant impact on their children's learning outcomes. According to the study's findings, the descriptive analysis indicated that the data fell into four categories: high (26.31%), moderate (21.05%), sufficient (36.74%), and low (15.78%). In contrast, the t-value from the inferential analysis was 12.466 with a significance level of 0.000.